The Effect of Word Square Model on Students Vocabulary at Grade X of SMK Tamansiswa Sukadamai in Academic Year 2019/2020 - Ginting, Datulina; Sidabalok, Inawaty; ., Rumondang (KnE Social Sciences, 2023)
The title of this study is the effect of word square model on students’ vocabulary at grade X of SMK Tamansiswa Sukadamai in Academic Year 2019/2020. The objectives of the study is to describe how the implementation of teaching english vocabulary by using word square at SMA.N.1. Buntu Pane. The population of this research was taken from the grade X students at SMK Tamansiswa Sukadamai, which have 102 students. The data were collected by using 10 essay question. Several steps of work have been done preliminary. The further steps is to follow the active concerning with the data. Starting from library check, confirming the location, asking permission from the pre-test and post-test value that worked by students in experiment class and control class are very significant. The data were analyzed by t-test. The result of students’ vocabulary. It was suggested that using media in teaching can made the students feel enjoy when they study about vocabulary and according to this skripsi the teacher can increase their teaching skill. Keywords: Word square model; students’ vocabulary; media in teaching